Stable isotopes and human diet in central western Argentina - Gil, Adolfo Fabian (2011)
Central western Argentina is the southern boundary of prehispanic maize in the archaeological record.This paper explores the stable isotope information from human bone (d13C, from collagen and d13C from apatite) and tooth (d13C from enamel) samples in order to characterize the temporal and spatial trends of these isotopes and to understand them in terms of human diet.We analyzed 104 human individuals from the last 6000 years. Using the Kellner and Schoeninger (2007) model the results shows a high variation in human diet with few human individuals with a notably high significance of C4 plants (probably maize) as an energy source and these samples have a chronology around ca. 1000 years BP. On the other hand a high variation in an individual’s dietary life history is shown by differences between d13C collagen, apatite and enamel.d13C, from collagen and d13C from apatite) and tooth (d13C from enamel) samples in order to characterize the temporal and spatial trends of these isotopes and to understand them in terms of human diet.We analyzed 104 human individuals from the last 6000 years. Using the Kellner and Schoeninger (2007) model the results shows a high variation in human diet with few human individuals with a notably high significance of C4 plants (probably maize) as an energy source and these samples have a chronology around ca. 1000 years BP. On the other hand a high variation in an individual’s dietary life history is shown by differences between d13C collagen, apatite and enamel.